Mathematical relationships in education [ identities and participation - Black, Laura , 1975-; Mendick, Heather; Solomon, Yvette (Routledge research in education, 2009)
While demand for the mathematically literate citizen increases, many learners continue to reject mathematics and experience it as excluding and exclusive, even when they succeed at it. In exploring this phenomenon, this volume examines the ways in which learners form particular relationships with mathematics in the context of formal schooling.